Propuesta De Diseño Arquitectónico De Espacios Agro Productivos Sostenibles En Las Comunidades Arroceras Del Juncal Huila - Camacho Guevara, Germán David (Universidad Antonio Nariño, 2022)
The following work is developed in the extension of the Juncal, municipality of Palermo, a territory which has been the scene of high concentration and growth of rice and paddy activities, lending itself to the development of a research work that allows to analyze in depth the current problems that plague the rice farming sector in general, and from this analysis, a research question is developed that allows to direct the project, being this the one of: How to design sustainable agro-productive spaces that guarantee stability and mitigate the problems that small rice producers of Juncal - Huila presently have? With this established, the project seeks to provide a practical solution to the elements found today, developing alternatives and exposing highly relevant characters from the analysis and referential interventions that allow to conclude with a specific architectonic alternative, taking into account theoretical and conceptual elements for the improvement of the rice culture of the territory.